2019
DOI: 10.1097/md.0000000000015166
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism is an independent risk factor for Menière's disease

Abstract: The relationship of hypothyroidism and Menière's disease (MD) has been discussed before, yet not well documented. Our study aims to investigate the correlation of both diseases. This is a retrospective cohort study based on data from the LHID2000 (Longitudinal Health Insurance Database 2000), a subset of the Taiwan National Research Health Insurance Database that contains claims data for the 2000 to 2011 period. A total of 27,050 patients were included in this study, 5410 of whom had received a hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
(26 reference statements)
0
12
1
Order By: Relevance
“…The future clinical implications of the beneficial effect of TH on vestibular compensation for therapy of patients with acute vestibular loss can be two-fold: (1) Similarly to the current rat experiments, L-T4 could be administered in the acute phase of vestibular syndrome to reduce symptoms of vestibular asymmetry and accelerate vestibular compensation. The translation to clinical practice is facilitated by the widespread availability of L-T4 medication; (2) pre-existing hypothyroidism may be considered as a risk factor for poor vestibular compensation or vertigo, which should be screened more regularly [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The future clinical implications of the beneficial effect of TH on vestibular compensation for therapy of patients with acute vestibular loss can be two-fold: (1) Similarly to the current rat experiments, L-T4 could be administered in the acute phase of vestibular syndrome to reduce symptoms of vestibular asymmetry and accelerate vestibular compensation. The translation to clinical practice is facilitated by the widespread availability of L-T4 medication; (2) pre-existing hypothyroidism may be considered as a risk factor for poor vestibular compensation or vertigo, which should be screened more regularly [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another small case series, the thyroxin medication improved the symptoms of Ménière’s disease patients with hypothyroidism (100%, 12/12) 24 . A cohort study conducted among 27,050 individuals in Taiwan demonstrated a 1.31-fold higher odds for hypothyroidism in patients with Ménière’s disease (95% CI 1.14–1.51) 16 . However, they did not consider other thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathophysiologic causes for the increase of endolymphatic flow are not understood and are thought to be multifactorial, including abnormal immune response and metabolic endocrine dysfunctions, such as hypothyroidism 13 15 . Previous studies have suggested the association of hypothyroidism with Ménière’s disease 14 , 16 , 17 . To our knowledge, there has been little research on thyroid diseases for a relationship with Ménière’s disease.…”
Section: Introductionmentioning
confidence: 94%
“…A previous study revealed that the average annual prevalence of MD was 34.5% and the average annual incidence of MD was 5.0 per 100,000 populations [ 2 ]. The overall incidence of MD was found to be significantly higher in a hypothyroidism cohort 8.65 per 1000 person-years versus a non-hypothyroidism cohort 6.38 per 1000 person-years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since both hypothyroidism and MD share a common pathophysiology of autoimmunity, former studies have proved the relationship between hypothyroidism and MD [ 3 , 13 , 17 ]. Other studies found hearing impairment in patient with Pendred syndrome as well as patients with acquired hypothyroidism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%